A randomized and controlled trial about the use of oral isotretinoin for photoaging - Bagatin, Ediléia; Parada, Meire O.B.; Miot, Hélio Amante [UNESP]; Hassun, Karime M.; Michalany, Nilceo; Talarico, Sergio (Wiley, 2010)
Topical retinoids are used to treat photoaging; oral isotretinoin is gold standard for acne; off label indications, including photoaging, have been reported with insufficient evidence of efficacy. This is a randomized controlled phase II trial with clinical and histological assessment to evaluate efficacy and safety of oral isotretinoin for photoaging. Study population was comprised of 32 menopausal or sterilized women, aged 40-55, divided in 2 groups: A (21) received 20mg isotretinoin, 3 times per week, nightly moisturizer, and daily sunscreen, for three months; B (11) just moisturizer/sunscreen. Main outcome measures were: overall clinical assessment; profilometry, corneometer and elasticity tests in periocular regions and left forearm; before/after biopsies from left forearm in patients of B and in 10 randomly selected of A. Microscopic blinded evaluation of epidermal thickness, dermal elastosis, new collagen, p53 epidermal expression was performed by quantitative digital image analysis. All data were submitted to statistical analysis. Clinical evaluation showed slight improvement; profilometry, corneometer and skin elasticity tests presented significant difference in pre/post values (P = 0.001 to 0.028), but no differences between A/B. Histological findings and p53 expression were comparable between groups before treatment (P > 0.1); microscopic analysis showed no differences between groups for most variables, after treatment. Slight but significant difference between A/B for p53 with major reduction post isotretinoin [0.66±0.31 vs. 0.94±0.34 respectively (P = 0.04) was observed. There were minor side effects and no significant laboratory test alterations. We concluded that no significant clinical, microscopic changes but p53 epidermal expression reduction were observed. The role of ultra-violet induced p53 mutation in skin carcinogenesis reinforces retinoids chemoprevention. Oral isotretinoin seemed safe but not effective to treat photoaging. Caution should be considered for women prone to pregnancy. Further controlled studies are necessary. © 2010 The International Society of Dermatology.
Keywords: collagen; isotretinoin; protein p53; sunscreen; adult; cheilitis; clinical article; clinical assessment; clinical trial; controlled clinical trial; controlled study; depression; drug efficacy; drug safety; drug use; dry nose; elasticity; epidermis; female; female sterility; histology; human; human tissue; image analysis; irritant dermatitis; menopause; phase 2 clinical trial; photoaging; protein expression; randomized controlled trial; side effect; skin biopsy; skin test; skinfold thickness; xerophthalmia; xerostomia; Administration, Oral; Adult; Analysis of Variance; Dermatologic Agents; Dose-Response Relationship, Drug; Double-Blind Method; Esthetics; Female; Follow-Up Studies; Humans; Isotretinoin; Middle Aged; Patient Satisfaction; Probability; Risk Assessment; Skin Aging; Statistics, Nonparametric; Treatment Outcome